Studies in the History of Tax Law, Volume 6 - Tiley, John (Studies in the History of Tax Law, 2013)
These are the papers from the 2012 Cambridge Tax Law History Conference revised and reviewed for publication. The papers include new studies of: income tax law rewrite projects 1914-1956; law and administration in capital allowances 1878- 1950; the 'full amount' in income tax legislation; Sir Josiah Stamp and double income tax; early German income tax treaties and laws concerned with double tax avoidance (1869-1908); the policy of the medicine stamp duty; 'Danegeld' - from Danish tribute to English land tax; religion and charity, a historical perspective; 'Plaintive Glitterati'; a collision of accounting and law, dividends from pre-1914 profits in Australia; the history and development of the taxation profession in the UK and Australia; an inquiry into Dutch to British Colonial Malacca 1824-1839; the taxation history of China; taxing bachelors in America: 1895-1939; Dutch Tax reform under Napoleon; and the last decade of estate duty.